PENGEMBANGAN MEDIA PEMBELAJARAN TOEFL READING BERBASIS VIDEO MIND MAP UNTUK MAHASISWA IAIN SURAKARTA - Fithiryah Nurul Hidayati (Universitas Islam Balitar, 2015)
The objective of this study is to map reading 4 materials in a mind map framework and visualizing the materials in the video program for TOEFL reading materials on mid map basis for TOSE students at IAIN Surakarta. The study used Research and Development (R&D) assigning TOSE students and lecturers in the program. Three stages of R&D devised by Borg & Gall (2003) were implemented in the study, covering: exploration, development of prototype, and effectiveness assessment of the product. The study found the following findings. First, exploration stages commenced from needs analysis and development of initial prototype. Second, the development of prototype began with devising reading materials in a video program on the basis of mind map. Prototype was evaluated based upon expert judgement and main field testing resulting revision on the teaching materials. Third, Mind Map-Based TOEFL Reading materials gives better results than reading materials of conventional version.